Dearomatization of 3‐Nitroindoles by a Phosphine‐Catalyzed Enantioselective [3+2] Annulation Reaction. (18th March 2019) - Li, Kaizhi; Gonçalves, Théo P.; Huang, Kuo‐Wei; Lu, Yixin
Abstract: The dearomatization of 3‐nitroindoles through a chiral‐phosphine‐mediated [3+2] annulation reaction is described. This method makes use of readily available 3‐nitroindoles as an aromatic feedstock and rapidly delivers a wide range of cyclopentaindoline alkaloid scaffolds in a highly enantioselective manner. Notably, phosphine‐triggered cyclization has not been utilized previously in a dearomatization process.